Role of eelgrass on bed-load transport and sediment resuspension under oscillatory flow - Marin-Diaz, Beatriz; Bouma, Tjeerd J.; Infantes, Eduardo (John Wiley and Sons Inc., 2019)
Coastal vegetation is widely attributed to stabilize sediment. While most studies focused on how canopy causes flow reduction and thereby affects sediment dynamics, the role of roots and rhizomes on stabilizing the surface sediment has been less well studied. This study aims to quantify interactions between above- and belowground biomass of eelgrass (i.e., living Zostera marina plants and mimics) with surface sediment erosion (i.e., bed load and suspended load), under different hydrodynamic forcing that was created using a wave flume. Belowground biomass played an important role preventing bed-load erosion, by roughly halving the amount of sediment transported after being exposed to maximal orbital velocities of 27 cm s−1, with and without canopy. Surprisingly, for suspended sediment transport, we found opposite effects. In the presence of eelgrass, the critical erosion threshold started at lower velocities than on bare sediment, including sand and mud treatments. Moreover, in muddy systems, such resuspension reduced the light level below the minimum requirement of Z. marina. This surprising result for sediment resuspension was ascribed to a too small eelgrass patch for reducing waves but rather showing enhanced turbulence and scouring at meadow edges. Overall, we conclude that the conservation of the existent eelgrass meadows with developed roots and rhizomes is important for the sediment stabilization and the meadow scale should be taken into account to decrease sediment resuspension.
Keywords: Oceanography; Aquatic Science